(untitled) (Research, Society and Development, 2021)
Although tooth eruption is considered a physiological process, Pediatric Dentists are often questioned about possible changes resulting from irruption. The objective of this paper is to present a case of delayed eruption of maxillary central incisors in an 8-year-old male child. Due to the pandemic, and the advice of government agencies to suspend elective dental care, the conduct was to use telemonitoring to monitor, advise and accommodate the patient. During the consultations, remotely, it was possible to observe that the patient’s gums were fibrosed, since the child presented early loss of deciduous teeth. With the images provided by the mother, it was possible to observe in the region of teeth 11 and 21 a gingival bulging. After 3 months of follow-up, the teeth erupted, presenting a spontaneous clinical resolution, with minimal intervention. Thus, we conclude that a good diagnosis made by the dental surgeon is essential for successful clinical management and the use of telemonitoring was a powerful and safe tool at this time of pandemic, allowing remote monitoring of children with oral health care.